REDUCED WEIGHT AUTOMOTIVE BRAKE PEDAL TEST & ANALYSIS - Bahadir Kuday; Orcun Yontem; Volkan Pestelli; Kerem Dagdelen; Ilknur G. Sahin; Sefa Kale; Alp Tekin Ergenc; Ali Fuat Ergenc (International Journal of Automotive Science and Technology, 2017)
Currently, automotive industry continues to strive for light weight vehicle for improving fuel efficiency and emission reduction. It is crucial to design vehicles with an optimum weight for a better performance of the car. In this field, which has boundaries with fixed standards and regulations, manufacturers continue to work on characteristics, structures and types of the material to develop  new components, which have same safety specifications but cheaper and lighter than current products.